Pengaruh Ekstrak Sarang Semut (Myrmecodia Sp) dalam Pengencer Ringer Laktat Terhadap Abnormalitas dan Viabilitas Spermatozoa Ayam Kampung: The Effect of Sarang Semut (Myrmecodia Sp) Extract in Ringer Laktat Dilution on the Abnormality and Viability of the Spermatozoa of Ayam Kampung (Gallus gallus) - Kiki Inggriani; Angelina Novita Tethool; Sintje Lumatauw (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
Antioxidants can inhibit the oxidation process by reacting with free radicals, which in turn, maintain the quality of spermatozoa. This study aims to determine the viability and the abnormality of â€œayam kampungâ€ (Gallus gallus) spermatozoa after being diluted in ringer lactate infused with â€œsarang semutâ€ (Myrmecodia Sp) extract. RAL is the research method used, utilizing 4 different Gallus gallus as test subjects. The variables observed are the abnormality and the viability of the spermatozoa sample treated with different amounts of Myrmecodia Sp extract, P0: 0 ml, P1: 0.02 ml, P2: 0.03, and P3: 0.04 ml. The abnormality rate for each sample is as follows; P0: 14 Â± 4.05%, P1: 13.5 Â± 3.78%, P2: 3.5 Â± 1.23% and P3: 12.83 Â± 5.04 %. Using the variance analysis, the result showed that the addition of Myrmecodia Sp extract in ringer lactate solution had little to no effect on causing spermatozoa abnormalities. Furthermore, the viability of spermatozoa for each sample is; P0: 14 Â± 4.05%, P1: 13 Â± 3.78%, P2: 13 Â± 1.22% and P3: 12 Â± 5.04%. Based on the variance analysis, the result showed that Myrmecodia Sp extract had a significant effect (P <0.05) on the spermatozoa viability. The addition of Myrmecodia sp extract to ringer lactate diluter had little to no effect on the abnormality of the Gallus gallusâ€™ spermatozoa but had a significant effect on the spermatozoaâ€™s viability.